Reversible Visualization for Synchrotron Radiation Using Photochromic Dye and Photostimulable Phosphor Composite Film - Kenji Kinashi; Kazuya Jimbo; Takahiro Okabe; Sono Sasaki; Hiroyasu Masunaga (International Journal of Photoenergy)
The study reported herein is undertaken to visualize reversibly synchrotron radiation by using a composite film comprised of two components: a photochromic SP with the conversion characteristics of UV-to-visible color and PSP BaFCl:Eu2+ particles with the conversion characteristics of X-rays-to-UV emission.